Carry‐over effects of winter habitat vary with age and sex in yellow warblers Setophaga petechia. (18th March 2013) - Drake, Anna; Rock, Christine; Quinlan, Sam P.; Green, David J.
<x xml:space="preserve">Abstract</x> We use stable isotope data to investigate the role of winter habitat use in altering the breeding phenology of yellow warblers Setophaga petechia. We first confirm that δ13C and δ15N isotopic signatures vary with winter habitat use in this species. We then examine the relationship between winter habitat use, breeding phenology and productivity within four age‐sex‐classes, since life history theory would predict that carry‐over effects should vary with age and gender. The δ13C signatures of yellow warblers using riparian habitats over winter were more depleted than the signatures of those using agricultural or scrub habitat. Individuals on the Pacific coast of Mexico were also more δ15N enriched than those on the southern Gulf of Mexico. δ13C and δ15N signatures were only correlated with earlier clutch initiation and subsequent higher productivity in first‐breeding‐season females. We estimate that shifts in δ13C equivalent to a shift from scrub to riparian winter habitat would be associated with the production of 0.8 more fledglings by yearling females. Pre‐breeding events that influence the timing of breeding could also influence the reproductive performance of older males and females, but we found little evidence that winter habitat use influenced breeding season phenology in these birds.